Antimicrobial, cytotoxicity, molecular modeling and DNA cleavage/binding studies of zinc-naproxen complex: switching DNA binding mode of naproxen by coordination to zinc ion. Issue 9 (23rd May 2022) - Khandar, Ali Akbar; Mirzaei-Kalar, Zeinab; Shahabadi, Nahid; Hadidi, Saba; Abolhasani, Hoda; Hosseini-Yazdi, Seyed Abolfazl; Jouyban, Abolghasem
Abstract: The intercalation DNA binding mode of the naproxen, a non-steroidal anti-inflammatory drug, has been reported previously. In this study, calf thymus deoxyribonucleic acid (CT-DNA) binding of zinc-naproxen complex, [Zn(naproxen)2 (MeOH)2 ], at physiological pH has been investigated by multi-spectroscopic techniques and molecular docking. Zinc-naproxen complex displays significant binding property to the CT-DNA ( Kb = 0.2 × 10 5 L.mol −1 ). All of the experimental results; relative increasing in viscosity of CT-DNA and fluorimetric studies using ethidium bromide (EB) and Hoechst 33258 probes, are indicative of groove binding mode of zinc-naproxen complex to CT-DNA. These results show that the coordination of naproxen to zinc metal switches the mode of binding from intercalation to groove. The molecular modeling also shows that the complex binds to the AT-rich region of minor groove of DNA. Structural and topography changes of DNA in interaction with the complex by atomic force microscopy (AFM) indicated that CT-DNA becomes swollen after interaction. The pUC18 plasmid DNA cleavage ability of zinc-naproxen complex by gel electrophoresis experiments revealed that zinc-naproxen complex cleaved supercoiled pUC18 plasmid DNA to nicked DNA. The cytotoxicity of the zinc complex performed by MTT method on HT29 and MCF7 cancer cell lines and on HEK 293 normal cell lines indicates that zinc complex has no cytotoxic effect on both HT29 and MCF7 cell lines but has better cytotoxicity effect on HEK 293 cell lines compared to cisplatin standard drug. The antimicrobial activity of the complex against Staphylococcus aureus and Escherichia coli bacteria revealed the high antimicrobial activity of the complex. Communicated by Ramaswamy H. Sarma